Study on some properties of the hybrid cell B4D10C9 producing the anti B monoclonal antibody which was agglutinated the b antigens on the surface of red blood cells - Trung, Nguyễn Thị; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2018)
The B4D10C9 hybridoma cell line producing the monoclonal antibody which was specifically agglutinated red blood cells B group, belongs to the IgM class and kappa light chains that have been created in our previous study. This study presents some biological charateristics of B4D10C9 such as the capability of growth, anti B monoclonal antibody producing, the stability of growth and cell line and antibody secreting of this cell line. The hybridoma cells grew well in the DMEM medium added with fetal bovine serum (FBS) at the final concentration of 1% or 10%. However, the maximum density of cells reached 9,9 x 105 cells per ml after 50 hours post incubation only when it was cultured in the medium containing 10% of FBS. The maximum antibody titers in the supernatant that collected after 150 hours of culture reached 1/512. In contrast to that, the maximum density of cells only reached 3,4 x 105 cells/ml after 72 hours post incubation when was cultured in DMEM medium containing 1% FBS. The maximum antibody titer was 1/64 after 50 hours post incubation. These cells were cultured through 3 different generations and the ability of antibody production in each generation was evaluated. As a result, this cell line had continuous growth stability and antibody secretion through 3 generations. The quantity of monoclonal antibody obtained from the supenantant of the culture medium at 150 hours of incubation was about 100 micrograms per ml. Thus, the growth of the cell line B4D10C9 and its ability of secretion of anti B monoclonal antibody were better when was cultured in the DMEM medium containing 10% fetal bovine serum. Preservation, storage and recovery does not affect to the growth and antibody producing of this cell line.